2020
DOI: 10.1093/ehjci/ehaa946.1861
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of VA-ECMO and IMPELLA (ECPELLA) as a possible strategy to improve outcomes in patients who underwent E-CPR

Abstract: Background Extracorporeal Cardio-Pulmonary Resuscitation (E-CPR) is an effective tool for patients with refractory cardiac arrest (CA). Since VA-ECMO provides strong afterload, IABP is often used to increase left ventricular load. Recently, in Japan, the effectiveness of VA-ECMO in combination with IMPELLA, a forward flow mechanical circulatory support device (ECPELLA) is gaining attention. Purpose We investigated usefulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…14 If LV distension is detected, there are several ways of reducing afterload, including placement of an Impella device (so-called ECPELLA). 15 Fortunately, in our patient, the pulmonary artery diastolic pressure consistently remained < 22 mm Hg.…”
Section: Discussionmentioning
confidence: 49%
“…14 If LV distension is detected, there are several ways of reducing afterload, including placement of an Impella device (so-called ECPELLA). 15 Fortunately, in our patient, the pulmonary artery diastolic pressure consistently remained < 22 mm Hg.…”
Section: Discussionmentioning
confidence: 49%
“…A retrospective cohort study of matching 58 ECPella and 58 VA-ECMO patients in refractory CS observed that during the first 72 hours following initiation of VA-ECMO, the ECpella group had significantly higher mechanical circulatory flow support and had reduced catecholinergic pharmacologic support compared to the VA-ECMO alone group. Furthermore, the 30-day and 1-year survival rates were also noted to be significantly higher in the ECPella group [25].…”
Section: Impellamentioning
confidence: 86%